KOMUNIKASI DAN ADVOKASI DALAM MEMBANGUN KOMITMEN PEMBANGUNAN PERKOTAAN BERKELANJUTAN MELALUI MULTI-STAKEHOLDER PARTNERSHIP DI PROVINSI LAMPUNG - Aulia Rahmawati; Fritz Akhmad Nuzir; Kustiani; Aditya Mahatidanar Hidayat; Okta Ainita (Jurnal Perencanaan dan Pengembangan Kebijakan, 2025)
Sustainable urban development can support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 11, and can be optimized through multi-stakeholder collaboration. This paper aims to (1) Raise awareness among various parties about the importance of collaboration for sustainable cities and communities; (2) Advocate for active support from pentahelix stakeholders (government, private sector, academia, community, and media) through the principles of Multi-Stakeholder Partnerships (MSP); and (3) Strengthen institutional commitment to collaborative governance in achieving SDG 11 in Lampung Province. The research employs a descriptive qualitative method to examine the dynamics of communication and advocacy in cross-sectoral collaborative processes. Data collection was conducted through a series of audience meetings with various stakeholders, including government institutions, academia, civil society organizations, local communities, and the media. The findings conclude that the success of building sustainable cities and communities largely depends on strategic communication and systematic, participatory advocacy processes. The multi-stakeholder partnership (MSP) approach involving the pentahelix elements—government, academia, community, media, and the private sector—has proven to provide an inclusive and practical framework for collaboration. However, realizing sustainable urban development in Lampung Province still faces significant challenges, particularly rgarding slum settlement issues that require special attention.